PENGARUH RADIASI PLASMA DAN PUPUK KANDANG KAMBING TERHADAP PERTUMBUHAN BAWANG MERAH VARIETAS BIMA BREBES - Emi Anitasari; Erma Prihastanti; Fajar Arianto (Universitas Medan Area, 2019)
Shallot variety of Bima Brebes is a shallot variety that is widely cultivated by farmers in Indonesia because it is easy to grow and adapt to the local environment. However, in reality many farmers use the previous harvest for the next planting seed so that the yields obtained will be of poor quality. This study aims to determine the effect of giving nitrogen through corona incandescent plasma discharge and goat fertilizer on the growth of shallots so that it can improve the quality of onion seedlings. This study used a Completely Randomized Design (CRD) with a factorial pattern using a corona incandescent plasma discharge factor and goat manure. The results showed an interaction between the two factors that can be seen from the plant height parameters which showed significant results in the treatment of plant seeds that were plasma radiation for 30 minutes and the planting media were given goat manure 65 g. Based on the results of the study it can be concluded that the administration of corona incandescent plasma discharge and goat manure on the cultivation of shallots varieties of Bima Brebes was able to accelerate the time of sprouting by 200.3% and increase the growth of onion plants.